Isolated primary extranodal lymphoma of the oral cavity: A series of 15 cases and review of literature from a tertiary care cancer centre in India - Gunjan H Shah; Sajid Khan Panwar; Pankaj P Chaturvedi; Shubhada N Kane (Indian Journal of Medical and Paediatric Oncology)
Background: Non-Hodgkin′s lymphomas (NHL) have a great tendency to affect organs and tissues that do not ordinarily contain lymphoid cells. Involvement of the oral cavity by NHL is very rare. Materials and Methods: Retrospective analysis was carried out by chart review of patients who presented to our hospital between 1990 and 2008. All those patients whose histopathology at our hospital was confirmed as lymphoma were included. Results: Although we register nearly 2000 new oral cancers every year, most of which are squamous cell cancers, we could trace only 15 cases of oral lymphoma in the last 18 years. Of these, hard palate and alveolus were most common sites (5 each). The median age at presentation was 42.6 years. A vast majority (12/15) were NHL. Most patients (70%) reported with painless progressive swelling without systemic signs, such as fever, weight loss, and so on. Only 2 patients were HIV positive. Nearly two thirds received combinations of CT and RT. Cyclophosphamide, hydroxydaunorubicin, oncovin (vincristine), prednisolone regime was the most common regime offered (12/15). Most of them (67%) had good response to 6 cycles of CT that was followed by RT. 10/15 patients completed treatment. Follow-up data of more than 2 years of follow-up was present in 11/15 patients. With median follow-up of 27 months, 5 were disease free, 5 died, and 1 controlled following 2nd line of CT, 2 were lost to follow-up and 2 were alive with disease. Discussion: Head and neck lymphoma is the second most common region for extranodal lymphoma. The nasopharynx, tonsils, and base tongue are most often involved. Unlike the western world, oral cavity involvement is extremely rare. Interestingly, only 2 patients tested positive for HIV and most were young patients. Oral lymphoma may mimic benign oral conditions that often lead to misdiagnosis. Conclusion: Although oral cavity may be the preferred site of NHL in immunocompromised patients it does occur in immunocompetent patients as well. Isolated oral lymphoma is extremely rare and from our data we can say that oral NHL in Indian sub population is more aggressive compared with western literature.